Relasi Pedagang Asongan dan Wisatawan di Kawasan Ekonomi Khusus (KEK) Mandalika, Lombok, Nusa Tenggara Barat - Hakim, Latifa Dinar Rahmani; Satya Parama, I Dewa Made; Hilmi, Farida (Indonesian Journal of Tourism and Leisure, 2024)
Comfort and safety are one of the important aspects in supporting tourism development. However, this is also inversely proportional when visiting the KEK Mandalika which is a potential tourism destination on Lombok Island. This discomfort occurs because of hawkers who are considered too aggressive when peddling their wares. Through the phenomenon of hawkers in the KEK Mandalika, this study aims to see the process of interaction and relationships established between hawkers and tourists. With a qualitative phenomenological approach, the results showed that the social relations of traders are divided into two, namely between traders and traders and traders with tourists. It is this interaction between merchants and tourists that sometimes leads to negative interactions. So that in the process of interpreting meaning, it allows for negative labeling or perception given to hawkers. In fact, the interaction that is considered aggressive occurs because of several invisible factors such as the existence of certain needs or motives such as the need to spend merchandise to be deposited with distributors.